(untitled) (Interdisciplinary Studies Journal, 2024)
The Covid-19 pandemic brought significant challenges to education, especially to Rural Education, where access to the internet and technology can be more limited. This article aims to investigate the development of teaching methodologies in the context of the Covid-19 pandemic in rural schools, with the Donatila Barriga school in Colares-PA chosen as the research site. Methodologically, it is characterized as qualitative research, conducted through field research. The data collection instruments were semi-structured interviews, which allowed for the analysis of the statements of the interviewees. The results of the research show the methodologies used by rural education teachers during the pandemic period and highlight that, during this time, teachers faced difficulties with access to technology, psychological strain, and neglect from the government.